Using Scratch and App Inventor for teaching introductory programming in secondary education. A case study. (2016) - Papadakis, Stamatios; Kalogiannakis, Michail; Zaranis, Nicholas; Orfanakis, Vasileios
Paradoxically, as the role and significance of computing have increased in society and the economy, and coding is recognised as the fourth literacy, the number of students attending a programming course is in decline. In an attempt to increase interest in computer science (CS), there has been made much effort in developing tools and activities as preliminary learning materials in schools and universities. App Inventor and Scratch strive to engage the novice users by allowing them to write programs about things that connect with their interests in contrast to more conventional programming. In this paper, we focus on the use of these two block-based programming environments as tools to facilitate learning programming for novices. In our analysis, both novice programming environments (NPEs) seemed to be attractive platforms for introducing fundamental concepts in computer programming and both look appealing for majors and non-majors as well.